Interplay of long non-coding RNAs and TGF/SMAD signaling in different cancers - Farooqi, Ammad Ahmad; Attar, Rukset; Qureshi, Muhammad Zahid; Fayyaz, Sundas; Sohail, Muhammad Imran; Sabitaliyevich, Uteuliyev Yerzhan; Nurmurzayevich, Sadykov Bolat; Yelekenova, Armida; Yaylim, Ilhan; Alaaeddine, Nada (Cellular and Molecular Biology, 2018)
Based on the exciting insights gleaned from decades of ground-breaking research, it has become evident that deregulated signaling pathways play instrumental role in cancer development and progression. Interestingly discovery of non-coding RNAs has revolutionized our understanding related to transcription, post-transcription and translation. Modern era has witnessed landmark discoveries in the field of molecular cancer and non-coding RNA biology has undergone tremendous broadening. There has been an exponential growth in the list of publications related to non-coding RNAs and overwhelmingly increasing classes of non-coding RNAs are adding new layers of complexity to already complicated nature of cancer. Regulation of TGF/SMAD signaling by miRNAs and LncRNAs has opened new horizons for therapeutic targeting of TGF/SMAD pathway. In this review we have set spotlight on central role of LncRNAs in modulation of TGF/SMAD pathway. Major proportion of the available evidence is underlining positive role of LncRNAs in contextual regulation of TGF/SMAD pathway. LncRNAs are vital to these regulatory networks because they provide a background support to make the TGF/SMAD mediated intracellular signaling more smooth or make transduction cascade more flexible in response to cues from extracellular environment. Therefore, in accordance with this notion, MALAT1, OIP5-AS1, MIR100HG, HOTAIR, ANRIL, PVT1, AFAP1-AS1, SPRY4-IT, ZEB2NAT, TUG1 and Lnc-SNHG1 have been reported to positively regulate TGF/SMAD signaling. In this review, we have focused on the regulation of TGF/SMAD signaling by LncRNAs and how these non-coding RNAs can be therapeutically exploited. Short-interfering RNA (siRNA) and natural products are currently being tested for efficacy against different LncRNAs. Nanotechnological strategies to efficiently deliver LncRNA-targeting siRNAs are also currently being investigated in different cancers.